LITERARY ANALYSIS OF "WHITE SHIP "BY CHINGIZ AYTMATOV’ AND "1984" BY GEORGE ORWELL: A COMPARATIVE STUDY (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2025)
This comparative study examines White Ship by Chingiz Aytmatov and 1984 by George Orwell, two significant works of the 20th century that reflect socio-political realities through symbolic storytelling. Although grounded in different cultural and historical contexts, both texts explore themes of power, oppression, loss of freedom, and the destruction of individual identity under authoritative systems. The research analyzes the authors’ use of characterization, narrative style, symbolism, and ideological critique to portray the conflict between personal ideals and totalitarian forces. Aytmatov highlights moral degradation and the loss of cultural values through the tragic fate of a child dreaming of a world of purity and hope, while Orwell presents a dystopian society where truth is manipulated and individuality is systematically erased. Through a comparative lens, the paper reveals how both writers warn against the consequences of dehumanization and the erosion of moral consciousness, emphasizing the necessity of freedom, compassion, and cultural memory. The findings contribute to a deeper understanding of how literature reflects society and serves as a tool for social critique and humanistic discourse.